Host range of mammalian orthoreovirus type 3 widening to alpine chamois - Besozzi, Martina; Lauzi, Stefania; Lelli, Davide; Lavazza, Antonio; Chiapponi, Chiara; Pisoni, Giuliano; Viganò, Roberto; Lanfranchi, Paolo; Luzzago, Camilla (Veterinary microbiology, 2019)
•MRV-3 has been identified from lung tissues of alpine chamois in Italian Alps.•Virus belongs to lineage III clustering with strains from dog, bat and diarrheic pig.•Whole genome sequence highlighted reassortment and lack of host specific barriers.•No respiratory symptoms neither lung macroscopic lesions were observed.•High seroprevalence was observed in chamois population during a five-years survey. Mammalian orthoreoviruses (MRV) type 3 have been recently identified in human and several animal hosts, highlighting the apparent lack of species barriers. Here we report the identification and genetic characterization of MRVs strains in alpine chamois, one of the most abundant wild ungulate in the Alps. Serological survey was also performed by MRV neutralization test in chamois population during five consecutive years (2008-2012). Three novel MRVs were isolated on cell culture from chamois lung tissues. No respiratory or other clinical symptoms neither lung macroscopic lesions were observed in the chamois population. MRV strains were classified as MRV-3 within the lineage III, based on S1 phylogeny, and were closely related to Italian strains identified in dog, bat and diarrheic pig. The full genome sequence was obtained by next-generation sequencing and phylogenetic analyses showed that other segments were more similar to MRVs of different geographic locations, serotypes and hosts, including human, highlighting genome reassortment and lack of host specific barriers. By using serum neutralization test, a high prevalence of MRV-3 antibodies was observed in chamois population throughout the monitored period, showing an endemic level of infection and suggesting a self-maintenance of MRV and/or a continuous spill-over of infection from other animal species.